An ARDL Analysis on the Internet Usage Rate and the Wealth of Malaysians - Chong, Fennee; Liew, Venus Khim-Sen (North Atlantic University Union, 2012)
The objective of this study is to examine the relationship between gross national income per capita and the internet usage rate per 100 people of an emerging economy Malaysia both in the short and long-run. Autoregressive Distributed Lag Modeling Approach (ARDL) was used to analyze the thirteen-year time series collected for these two variables. Empirical findings from the econometrics analysis reported a significant long-run and short-run relationship between these two variables. Hence, this study concludes that, enhancing internet usage among the public and private sectors is a pertinent strategy for Malaysia towards achieving a higher wealth status for its people.